Diagnostic Value of Serum Insulin-Like Growth Factor Binding Protein 7 (IGFBP7) in Colorectal Cancer - Qiu, Bo (Onco Targets Ther, 2020)
PURPOSE: High serum insulin-like growth factor binding protein-7 (IGFBP-7) has been found in several malignant tumors. Here, we aimed to assess the diagnostic potential of serum IGFBP7 in patients with colorectal cancer (CRC). PATIENTS AND METHODS: An enzyme-linked immunosorbent assay (ELISA) was performed to detect IGFBP7 level in the serum of 115 CRC patients and 107 healthy controls, and receiver operating characteristics (ROC) was used to evaluate the accuracy of diagnosis. RESULTS: The levels of serum IGFBP7 were significantly higher in CRC than those in normal controls (P < 0.001). With optimized cutoff of 2.050 ng/mL, IGFBP7 showed certain diagnostic value with specificity of 93.9%, sensitivity of 64.5% and an area under the curve (AUC) of 0.815 (95% CI: 0.754–0.877) in CRC. In early-stage CRC, IGFBP7 provided an AUC of 0.826 (95% CI: 0.757–0.896), a sensitivity of 64.5%, and a specificity of 95.8%. Furthermore, when compared with carcinoembryonic antigen (CEA), the accuracy of serum IGFBP7 in the diagnosis of CRC and early-stage CRC were significantly improved. Analysis of clinical data shows that there are no significant differences between IGFBP7 and clinical factors. CONCLUSION: Our study suggested that serum IGFBP7 might serve as a potential biomarker for early-stage CRC diagnosis.